ANALISIS REAKSI PASAR SEBELUM DAN SESUDAH PENGUMUMAN PEMBELIAN KEMBALI SAHAM (BUY BACK) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Saharia Rumatumia; Nur Hidayati; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study aims to analyze the market reaction before and after the announcement of a stock return purchase (buy back) at a company listed on the Indonesia Stock Exchange (IDX). In this research, the method used is event studies, the sampling method used is purposive sampling obtained from 48 real estate and property companies so 17 companies are used as samples. The analysis used is the analysis of trading volume activity average there are differences in abnormal returns before and after the announcement of share buyback, and there are differences in trading volume activity before and after the announcement of a share buyback.Keywords: Buy Back, Abnormal Return, Trading Volume Activity